How to know a person : the art of seeing others deeply and being deeply seen - Brooks, David, 1961- (Penguin Books, 2025)
If you are going to care for someone, you must first understand them. If you're going to hire, marry, or befriend someone, you have to be able to see them. If you are going to work closely with someone, you have to be able to make them feel recognized and valued. As David Brooks observes, "The older I get, the more I come to the certainty that there is one skill at the center of any healthy family, company, classroom, community or nation: the ability to see each other, to know other people, to make them feel valued, heard and understood." And yet we humans don't do this well. All around us are people who feel invisible, unseen, misunderstood. In How to Know a Person, Brooks sets out to help us to do better, posing questions that are essential for all of us. Driven by his trademark sense of curiosity, Brooks draws from the fields of psychology and neuroscience, and from the worlds of theatre, history, and education, to present a welcoming, hopeful, integrated approach to human connection. How to Know a Person helps readers become more understanding and considerate towards others; it helps readers find the joy that comes from being seen. Along the way it offers a possible remedy for a society that is riven by fragmentation, hostility, and misperception. The act of seeing another person, Brooks argues, is a profoundly creative act: How can we look somebody in the eye and see something large in them, and in turn, see something larger in ourselves? How to Know a Person is for anyone searching for connection, seeking to understand and yearning to be understood.